A Systematic Screening of Traditional Chinese Medicine Identifies Two Novel Inhibitors Against the Cytotoxic Aggregation of Amyloid Beta - Ma, Liang; Zheng, Jiaojiao; Chen, Huijing; Zeng, Xia; Wang, Shilin; Yang, Chen; Li, Xi; Xiao, Yushuo; Zheng, Ling; Chen, Hong; Huang, Kun (Frontiers in Pharmacology, 2021)
The toxic aggregates of amyloid beta (Aβ) disrupt the cell membrane, induce oxidative stress and mitochondrial dysfunction, and eventually lead to Alzheimer’s disease (AD). Intervening with this cytotoxic aggregation process has been suggested as a potential therapeutic approach for AD and other protein misfolding diseases. Traditional Chinese Medicine (TCM) has been used to treat AD and related cognitive impairment for centuries with obvious efficacy. Extracts or active ingredients of TCMs have been reported to inhibit the aggregation and cytotoxicity of Aβ. However, there is a lack of systematic research on the anti-Aβ aggregation effects of TCM components. In this study, we performed a systematic screening to identify the active ingredients of TCM against the cytotoxic aggregation of Aβ42. Through a literature and database survey, we selected 19 TCM herbals frequently used in the treatment of AD, from which 76 major active chemicals without known anti-amyloid effects were further screened. This took place through two rounds of MTT-based screening detection of the cytotoxicity of these chemicals and their effects on Aβ42-induced cytotoxicity, respectively. Tetrahydroxystilbene-2-O-β-D-glucoside (TSG) and sinapic acid (SA) were found to be less toxic, and they inhibited the cytotoxicity of Aβ42. Further studies demonstrated that TSG and SA concentration-dependently attenuated the amyloidosis and membrane disruption ability of Aβ42. Thus, we identified two novel chemicals (TSG and SA) against the cytotoxic aggregation of Aβ42. Nonetheless, further exploration of their therapeutic potential is warranted.